Fungsi Puasa Dalam Membina Kecerdasan Emosional Menurut Hadis-Hadis Rasulullah SAW - Novianti, Hanifah (SHAHIH (Jurnal Ilmu Kewahyuan), 2023)
The phenomenon that occurs is nothing but the result of a person's low awareness and faith in the values and benefits contained in fasting. Meanwhile, the low awareness and faith is caused by a lack of knowledge about the meanings and wisdom of fasting. Because everyone tends to dislike and dislike something that he doesn't know much about his goals and objectives. The purpose of this research is to find out how a person builds their emotional intelligence under any circumstances and anywhere, and also to find out how a person's awareness in understanding values -the values and functions contained in fasting according to the Hadith of the Prophet Muhammad. This study uses a research method that is content analysis, in which the data is sourced from the library (library research), which focuses on explaining theoretical studies on emotional intelligence, the verses of the Koran and the Hadith of Rasulullah SAW are relevant to fasting and the implications of fasting on emotional intelligence according to the Prophet Muhammad. Based on research conducted and obtaining findings that can be interpreted in this case, fasting is believed to increase emotional, mental and physical intelligence. If we fast with a calm and sincere spirit, it turns out that there are many benefits for us. Fasting can prevent sexual desire and physical lust. Lust itself is caused by emotions, so fasting can cause emotions to suppress sexual appetite. Because, fasting can foster or control emotions. So, fasting can affect a person's emotional intelligence.